Can social safety nets protect public health? The effect of India's workfare and foodgrain subsidy programmes on anaemia - Sudha Narayanan; Nicolas Gerber; Udayan Rathore; Karthikeya Naraparaju (University of Bonn, Center for Development Research (ZEF), 2017)
Can large-scale social safety nets be nutrition sensitive even if they do not explicitly incorporate health and nutrition as programmatic goals? This paper focuses on the consequences of a countrywide guaranteed workfare programme (MGNREGA) and subsidised food distribution scheme (PDS) in India for the prevalence of anaemia, examining whether individuals in districts with a broader reach of these mega-programmes are less likely to be anaemic. Using an Instrumental Variable (IV) approach to address the endogeneity of programme scale, we find that an individual residing in a district where the programmes have broader reach is less likely to suffer from all forms of anaemia and has a lower haemoglobin deficit from the benchmark suggested by the World Health Organisation (WHO) - ranging between 0.91 to 6.2 percentage points for a 10 percentage point expansion in programme scale. While the PDS seems to be more effective in reducing the incidence of mild anaemia than moderate or severe anaemia, while the strength of effects for MGNREGA seem to be the least for mild. These are catch-all effects that represent partial and general equilibrium impacts through multiple pathways. Programme interaction effects suggest the MGNREGA and PDS may be substitutes - associated improvements in anaemia for regions with higher PDS access (MGNREGA participation) are more pronounced when the scale of MGNREGA participation (PDS access) is low. There exist nonlinearities in these relationships, with the efficacy of both programmes varying across scales of implementation.
Keywords: C01; I10; I38; 330; safety nets; PDS; MGNREGA; India; anaemia